A review of challenges facing clinical water management in the Malaysian context - Suhaimi, Afiza Abdullah; Samsuddin, Niza; Abu Samah, Mohd Armi (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Given that clinical waste could cause environmental and health problems, an important subject that emerges concerns its management. This study employed a gap analysis approach to determine Malaysia’s challenges in relation to the management of clinical waste, as well as quo practices in the country. With the objective of analyzing the state of clinical waste management, some of the specific subjects that were investigated included recommendations, challenges, policies and legislation, technology, and the treatment of clinical waste. Notably, one of the crucial forces that were worth considering involved the economic status of the country, especially because of the role of this factor in determining trends in waste disposal and treatment. From the results, Malaysia needs an effective approach to clinical waste management, especially through healthcare establishments (HCEs). Also, the country needs a holistic approach involving steps such s the use of environmentally safe and sound technologies, occupational safety and health programs, and waste segregation and minimization.